TaqMan qPCR pushes boundaries for the analysis of millennial wood. (March 2017) - Gómez-Zeledón, Javier; Grasse, Wolfgang; Runge, Fabian; Land, Alexander; Spring, Otmar
Abstract: Millennial-old trees excavated from alluvial deposits or sampled from historical buildings are of high scientific value, e.g. for dating archeological wood as well as to reconstruct past climate variability. While chronologies are supported by isotopic measurements, climate reconstructions from year rings depend on reliable species identification and in some cases even specific populations should be differentiated. Such information could easily be provided by suitable DNA markers, given that DNA is available in appropriate amount and quality. Information from ancient DNA of wood remains is very scarce due to the difficulties in the extraction process, degradation of nucleic acids and the physical and chemical complexity of wood samples. We developed a new method to trace highly fragmented DNA by using a TaqMan qPCR assay, combined with a DNA extraction protocol specifically designed for wood. This approach resulted in a high rate of positive samples and provided sequence DNA information from subfossil oak wood up to 9000 years of age. Highlights: A successful DNA extraction protocol for subfossil and historical wood is described. A TaqMan qPCR system was developed for detection of Quercus DNA. DNA was positively amplified even from a 9000-year-old oak sample.